Ответ:
(x; y)=(1; 2) х+у=3
Пошаговое объяснение:
\left \{ {{2x+5y=12} \atop {x=-\frac{5}{3}+\frac{4}{3}y}} \right.\\\\2(-\frac{5}{3}+\frac{4}{3}y)+5y=12\\\\-\frac{10}{3}+\frac{8}{3}y+5y=12\\\\-\frac{10}{3}+\frac{23}{3}y=12\\\\ -10+23y=36\\\\ 23y=36+10\\\\23y=46\\\\y=46:23\\\\y=2" alt="\left \{ {{2x+5y=12} \atop {3x-4y=-5}} \right.=>\left \{ {{2x+5y=12} \atop {x=-\frac{5}{3}+\frac{4}{3}y}} \right.\\\\2(-\frac{5}{3}+\frac{4}{3}y)+5y=12\\\\-\frac{10}{3}+\frac{8}{3}y+5y=12\\\\-\frac{10}{3}+\frac{23}{3}y=12\\\\ -10+23y=36\\\\ 23y=36+10\\\\23y=46\\\\y=46:23\\\\y=2" align="absmiddle" class="latex-formula">
![x=\frac{5}{3}+\frac{4}{3}*2\\\\ x=-\frac{5}{3}+\frac{8}{3}\\\\ x=\frac{3}{3}\\\\ x=1 x=\frac{5}{3}+\frac{4}{3}*2\\\\ x=-\frac{5}{3}+\frac{8}{3}\\\\ x=\frac{3}{3}\\\\ x=1](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B5%7D%7B3%7D%2B%5Cfrac%7B4%7D%7B3%7D%2A2%5C%5C%5C%5C%20%20x%3D-%5Cfrac%7B5%7D%7B3%7D%2B%5Cfrac%7B8%7D%7B3%7D%5C%5C%5C%5C%20%20x%3D%5Cfrac%7B3%7D%7B3%7D%5C%5C%5C%5C%20x%3D1)
Сумма:
1+2=3